CORRELATION PROSTATE VOLUME AND INTERNATIONAL PROSTATE SYMPTOM SCORE IN BENIGN PROSTATIC HYPERPLASIA PATIENT - Almaasah, Miftahurrohmat; Pramana, Ida Bagus Putra; Tirtayasa, Pande Made Wisnu; Santosa, Kadek Budi (E-Jurnal Medika Udayana; Vol 14 No 03 (2025): E-Jurnal Medika Udayana, 2025)
Background: Benign Prostatic Hyperplasia is one of the most prevalent benign tumors in men. Even it is less life threatening, but the symptoms is affecting quality of life for patient. IPSS is a questionnaire that developed to identify patient’s therapeutic needs and response therapies. Total score of IPSS and prostate volume are used to determine modality of BPH patient’s treatment. This study aims to know the relation of prostate volume and the degree of IPSS, and the correlation of prostate volume with obstructive or irritative symptoms in BPH patient. Methods: This research method is a correlative analysis using a cross-sectional study approach. The subjects were chosen from patient’s medical record who went to the Urology Department of RSUP Prof. I.G.N.G Ngoerah Denpasar from January 2021 until December 2022 that fit in inclusion and exclusion criteria. The result is analyzed using Spearman’s correlation test. Results: From 19 BPH patients, found that the most cases were the prostate volume classification I (36.8%) and the IPSS score in moderate symptoms (67.9%). The result of Spearman’s correlation test was significant relation between prostate volume and IPSS (p=0.005) and the correlation between prostate volume and IPSS was strong (r=0.617). Correlation between prostate volume, obstructive symptoms, and irritative symptoms showed significant relation (p=0.001) and 0.002) and the correlation between prostate volume, obstructive symptoms, and irritative symptoms was strong (r=0.717 and r=0.657). Conclusion: IPSS, obstructive symptoms, and iritative symptoms strongly correlated with prostate volume. Keywords : benign prostatic hyperplasia, IPSS, prostate volume